Use of hyperbaric oxygenation in the combination therapy of posttransplant kidney patients in the early postoperative period - M. V. Romasenko; O. A. Levina; A. V. Pinchuk; R. V. Storozhev; O. N. Rzhevskaya (Трансплантология (Москва))
Background. Posttransplantation acute tubular necrosis (CTN) is mainly an ischemic injury caused predominantly by reperfusion syndrome, impaired microcirculation, and worsening hypoxia of a transplanted organ. Hyperbaric oxygenation (HBO) making possible the delivery of oxygen to organs and tissues, by dissolving it in the body’s fluids, is one of the methods for combating systemic and regional hypoxia underlying the development of ischemic graft injury.Objective: to evaluate the efficiency of HBO in the combination therapy of patients with severe ischemic kidney graft injury in the early postoperative period.Subjects and methods. The early postoperative period after kidney transplantation was comparatively analyzed in 2 patient groups: study (29 patients were given HBO sessions in the combination therapy) and control (24 patients receiving traditional therapy) ones. HBO sessions were carried out in single-person medical altitude chambers at 1.2-1.6 ATA for 40 min. A correlation analysis was made between cold graft ischemia time and indicators, such as recovered water excretory function, normalized azotemia level, the level of creatinine and urea, and the number of hemodialysis sessions in the above comparison groups.Results. The performed analysis has shown that there is a direct correlation between the parameters under study. In the study group, renal graft function recovered in the earlier periods than that in the control group.Conclusion. The early incorporation of HBO into combination treatment after kidney transplantation contributes to prompter recovery of graft function. The conducted study permits one to consider that HBO should be incorporated as soon as possible into the combination treatment performed in the early period after kidney transplantation.